Creutzfeldt-Jakob Disease: Atypical Presentation of a Very Rare Disease - Oliveira, Renato (2021)
Creutzfeldt-Jakob disease typically presents as rapidly progressive dementia. We describe the case of a 59-year-old male patient presenting with sudden onset of central facial palsy and dysarthria, followed by myoclonus of his left upper and lower limbs. Initial brain magnetic resonance showed hyperintensity of the right caudate and putamen on diffusion-weighted imaging and T2 sequences. Cerebrospinal fluid analysis showed increased protein count. The workup to investigate autoimmune, infectious and paraneoplastic causes was negative. Symptoms progressively worsened, with left hemiplegia, dysphagia, urinary incontinence, and, later, akinetic mutism. The follow-up brain magnetic resonance scan revealed hyperintensity of bilateral basal ganglia as well as cerebral cortical abnormalities on diffusion-weighted imaging. Electroencephalography showed periodic activity and tau protein levels in the cerebrospinal fluid were elevated. Genetic analysis showed mutation c-598G > A. The patient died four months later. We report a case of familial Creutzfeldt-Jakob disease with atypical clinical and radiological features, namely neurological focal signs with sudden onset, absence of significant cognitive impairment and unilateral radiological findings. With disease progression, characteristic clinical and radiological features led to the diagnosis.